Discharge documentation improvement project: a pilot study. Issue 12 (December 2015) - Tan, B.; Mulo, B.; Skinner, M.
Abstract: Background: Discharge summaries remain a critical communication tool with primary care physicians. In a previous study of over 200 general medicine discharge summaries, we demonstrated that only 50% contain information regarding the indication and follow up required of any medicine changes on discharge. Aim: In this follow up pilot study, we assess the role of feedback and token incentives in improving discharge documentation. Methods: Over a 14‐week period, we randomly audited a selection of discharge summaries on a fortnightly basis. The results of these audits were fed back to the junior medical staff who compiled these summaries. If over 80% of the audited discharge summaries adequately documented the indication, with required follow up for new medication changes, junior doctors were provided with a token, non‐monetary incentive for their efforts. At the end of the study period, we then conducted a survey of the junior doctors involved and collected feedback regarding their impressions of the study. Results: Over the study period, 722 discharge summaries were completed and eligible for analysis. Over this time, mean appropriate documentation regarding medicine indication improved by 32%, and follow‐up documentation improved by 10%. Overall, the participants felt the interventions were beneficial and that they should be continued beyond the study period. Conclusions: Education coupled with regular feedback and non‐monetary incentives can potentially lead to improvements in the quality of discharge summaries.